Fluorescence Spectroscopic Studies of in vitro Interactions of Famotidine and Tapentadol Hydrochloride with Bovine Serum Albumin - Md Rasal Hossain Khan; Md Zakir Sultan; Md Zamil Sultan; Mohammad A Rashid; Asma Abdul Rahman (Department of Pharmaceutical Sciences, University of Dhaka, 2024)
Indexed by Scopus